Steroid Response in Autoimmune Hemolytic Anemia - Nazneen, Shahela; Mahbub, Mohammad Imtiaj; Choudhury, Zulfia Zinat (Journal of Shaheed Suhrawardy Medical College, 2022)
Background: Auto-immune hemolytic anemia is an uncommon but not rare disorder. Steroid is the best and commonly used drug for this disorder because it is cheap, easily available and less toxic. But there are a few studies on evaluation of response of steroids in auto-immune hemolytic anemia in our country. Objectives: The purpose of the study was to find out the mean duration for attaining response with prednisolone at the dose of 1 mg/kg body weight, to categorize the patients according to response criteria and to find out the adverse effects due to prednisolone. Methodology: This was a longitudinal and prospective study done in Hematology department of Dhaka Medical College Hospital, Dhaka over a period of one and half year from January 2011 to July 2012. All diagnosed cases of auto-immune hemolytic anemia attending in the hematology department full filling the inclusion and exclusion criteria were included in the study. Data were collected by using a structured questionnaire after taking written consent and history and doing physical examination and relevant baseline investigations. Patients were followed up for two weeks and further physical examination and investigations were done during this time. Result: Mean age of the patient was 33.08 year. Most of the patients (33.33%) belonged to <20 year age group. Progressive pallor, weakness and anemia were the most prominent clinical features (100%), followed by jaundice (50%), splenomegaly (50%), dyspnea (45.8%), hepatosplenomegaly (33.33%), palpable lymph nodes (8.33%) purpuric spot (2%), bleeding manifestation (2%) and bloody diarrhea (2%). No cause of autoimmune hemolytic anemia was found in 43 (89.5%) patients. Among 5 patients with autoimmune hemolytic anemia 3 (6.25%) had non-Hodgkin’s lymphoma, 1 (2.08%) had chronic lymphocytic leukemia and 1 (2.08%) had ulcerative colitis. DAT (Direct antiglobulin test) was found positive in 36 patients (75%) and both DAT and indirect antiglobulin test were found positive in 12 patients (25%). Out of 48 patients 32 patients (66.66%) responded within one week and the rest 16 patients (33.34%) responded within two weeks of starting treatment. 43 patients (89.58%) showed complete response and the rest 5 patients (10.42%) showed partial response. Conclusion: Most of the patients responded completely within one week and no patients were found without response. So, Steroid (prednisolone) is very cheap and effective drug for the vast poor people of Bangladesh. J Shaheed Suhrawardy Med Coll 2021; 13(1): 41-45